Spatial and temporal variation of aseismic creep along the dilational jog of the West Valley Fault, Philippines: Hazard implications - Rimando, Rolly E.; Kurita, Katsumi; Kinugasa, Yoshihiro (Frontiers in Earth Science, 2022)
Accelerated creep, primarily through vertical displacement, has been occurring along fifteen (15) en-echelon faults belonging to a 15-km long and 1.5 km wide, N-S-trending dilational jog of the active West Valley Fault (or West Marikina Valley Fault), on the southeastern part of Metro Manila, Philippines. The much larger than known tectonic slip rates had been the only reliable evidence in support of excessive groundwater withdrawal as the trigger of creep in the 90s. Recently available groundwater extraction (1977-2019) could link more directly and consistently groundwater withdrawal to accelerated creep in the 90s. Twenty years (1999-2019) of precise displacement measurements could also reveal significant spatial and temporal links between slip rate changes and patterns of groundwater extraction. Our analysis shows that greater rates of vertical displacement are related to the timing of faster extraction rates. Variations in slip rates between the northern and southern measurement sites are due primarily to regional differences in groundwater extraction, which are influenced by differences in the implementation of water extraction reduction regulations. Proximity to the key source of groundwater recharge (Laguna Lake) is also an influencing factor. Although there are many unknowns inherent to this type of study, continued depressurization could induce static stress changes that could modulate the timescale of earthquake occurrence due to the natural course of stress-loading driven by regional tectonics. The current and potential effects of continued depressurization in the areas with high slip rates and surrounding regions are paramount considerations in crafting and implementing tighter and extended groundwater extraction regulations.